Experimental Study of Bamboo As A House Retrofitting Material For Developing Countries - Suhelmidawati, Etri; Zamzarena, Rekana; Adibroto, Fauna; Syofiardi, Syofiardi (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2017)
Earthquake is one of the main natural disasters which frequently occur in West Sumatra. Large earthquake September 30, 2009, has caused damage to the structure and caused many casualties. Due to this condition, this research was made to study bamboo as a house retrofitting material for developing countries. Mechanical and physical properties such as moisture content testing, testing density, testing of compressive strength and tensile strength were conducted. It is obtained from the test results, the highest compressive strength and tensile strength are 94.958 MPa and 183 MPa, showed by Betung bamboo. Shaking table test are also undertaken to investigate the seismic behavior of bamboo masonry wall. Two degree of masonry walls, 60° and 90° are tested in order to check the strength of masonry wall by direction of the coming of an earthquake. From the shaking table test, it was observed that a 60° masonry wall showed a better seismic performance than those of a 90° masonry walls. Small cracks were observed at 90° masonry walls after 20 seconds, while there was no crack at a 60° masonry wall. As a result of these test, using bamboo as a house retrofitting material could be chosen, both of technically and economically.